Analisis Peran Penyidik Pegawai Negeri Sipil Dalam Penanganan Kasus Perniagaan Dan Peredaran Satwa Yang Dilindungi Dalam Dan Luar Kawasan Hutan (Studi Kasus Di Seksi I Balai Gakkum Wilayah Sumatera Utara) - Junaidi, Junaidi; Joharsyah, Joharsyah; Sahbudi, Sahbudi (Jurnal Ilmiah Penegakan Hukum, 2025)
Analysis of the Concrete Role of Civil Servants in Handling Cases of Trade and Distribution of Protected Wildlife Within and Outside Forest Areas (Case Study in Section I of the North Sumatra Regional Law Enforcement Agency). This study aims to determine the role of civil servant investigators in Section I of the North Sumatra Regional Law Enforcement Agency in eradicating the crime of protected wildlife trade and also to identify the obstacles experienced by civil servant investigators in Section I of the North Sumatra Regional Law Enforcement Agency in preventing cases of trade and distribution of protected wildlife in North Sumatra. The type of research used is normative juridical research and an empirical juridical approach. Based on the results, it can be concluded that the role of civil servant investigators (PPNS) has a significant responsibility in carrying out investigations, inquiries, and law enforcement for violations of laws and regulations governing the protection and preservation of protected wildlife.